Oral health and use of dental services in different stages of adulthood in Norway: a cross sectional study - Elin Hadler-Olsen; Birgitta Jönsson (BMC, 2021)
Abstract Background Socioeconomic status and oral health care habits may change throughout adult life. This calls for age-stratified analyses of oral health in the adult population to uncover differences that could be of importance for organizing adequate oral health care services. The aim of the present study was to describe self-reported oral health in different age groups in a general adult population in Norway, and to explore associations between self-reported oral health and age groups, sociodemographic factors, use of dental services, number of teeth and dental caries. Methods We used data from a cross-sectional study of almost 2000 Norwegian adults, 20-79 years old. The study included both a structured questionnaire and a clinical examination to assess sociodemographic variables, use of dental services, self-reported oral and general health as well as dental caries and number of teeth. For analysis, the participants were divided into three age groups: young adults (20-29 years), middle-aged adults (30-59 years), and senior adults (60 years and older). Differences among groups were analyzed by cross-tabulation, and logistic regression analyses were used to assess associations between variables. Results Forty-eight percent of the participants rated their oral health as good. Almost half of the participants had at least one carious tooth, with the highest caries prevalence among the young adults. To be caries free was strongly associated with reporting good oral health among the young and middle-aged adults. One third of the senior adults had fewer than 20 teeth, which was associated with reporting moderate or poor oral health. Less than half of the young adults reported regular use of dental services, and 40% of them had postponed dental visits for financial reasons during the past 2 years. Regardless of age group, having to postpone dental visits for financial reasons or having poor-to-moderate general health were associated with high odds for reporting moderate or poor oral health. Conclusions That there were important age-group differences in self-reported and clinical measures of oral health and in the use of dental health services demonstrates the importance of age-stratified analyses in oral health research. Many adults, especially among the young, faced financial barriers for receiving dental health services, which was associated with poorer self-reported oral health. This argues for a need to revisit the financing of oral health care for adults in Norway.